Policy pathways for perennial agriculture - Scott, Emma I.; Toensmeier, Eric; Iutzi, Fred; Rosenberg, Nathan A.; Lovell, Sarah Taylor; Jordan, Nicholas R.; Peters, Tessa E.; Akwii, Esther; Broad Leib, Emily M. (Frontiers in Sustainable Food Systems, 2022)
Perennial agriculture refers to agricultural systems in which perennial crops are a central strategy for producing farm products and ecosystem services. Perennial agriculture offers a range of ecosystem services, including improved soil health and biodiversity, high carbon sequestration rates, agroecosystems better adapted to climate change, improved water quality, and economically viable products. Shifting U.S. agriculture to be perennial-focused will require a range of support structures, including federal policy changes. Federal policymakers should support perennial agriculture by establishing safety nets like those available for annual crops, centering perennial practices in cost-sharing conservation programs, facilitating market opportunities, and investing in perennial agriculture research and development.